Brain fables the hidden history of neurodegenerative diseases and a blueprint to conquer them - Espay, Alberto J. ca. 20./21. Jh; Stecher, Benjamin 1985- (Cambridge University Press, 2020)
An estimated 80 million people live with a neurodegenerative disease. That number is expected to increase rapidly as populations age, lifespans increase, and exposure to toxins rises. Despite decades of research and billions in funding, there are no medications that can slow, much less stop, the progress of these diseases. This is because diseases such as Parkinson's and Alzheimer's do not exist in biology. Yet, hundreds of clinical trials around the world are examining the potential of single therapies in thousands of people sharing one of these labels. Compounding the problem, these therapies were developed on evidence from models that do not come close to capturing the complexity of these diseases in the affected humans. These practices must end. Brain Fables is a call to refocus on understanding living and aging to create the personalized treatments each affected individual desperately needs